2016
DOI: 10.1007/s11356-016-7844-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of CaCO3-P coprecipitation on the leaf surface of Potamogeton crispus in water

Abstract: In this paper, the characterization of CaCO 3 -P coprecipitation on the leaf surface of Potamogeton crispus at various temperatures in pot experiments was investigated. White precipitates occurred on the leaf surfaces during the P. crispus growth period, and the chemical analysis demonstrates that the white precipitates contain Ca and P. The primary constituent of the white precipitates on the leaf of P. crispus was octacalcium phosphate (OCP) and hydroxyapatite. XRD characterization showed that the precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…The same results have been proven by Chen and Wang [14]. According to Liu et al [23], the precipitates on the surface of P. crispus were carbonate-containing hydroxylapatite. The difference in the SEM images of the precipitates on the surface of the two species (Figure 5) confirmed the specific differences in calcium and phosphorus coprecipitation.…”
Section: Composition and Variation In Ash Phosphorussupporting
confidence: 77%
See 1 more Smart Citation
“…The same results have been proven by Chen and Wang [14]. According to Liu et al [23], the precipitates on the surface of P. crispus were carbonate-containing hydroxylapatite. The difference in the SEM images of the precipitates on the surface of the two species (Figure 5) confirmed the specific differences in calcium and phosphorus coprecipitation.…”
Section: Composition and Variation In Ash Phosphorussupporting
confidence: 77%
“…In hard-water environments, most aquatic plants can precipitate carbonates (CaCO 3 ) [10,22] and exhibit calcification. Liu et al [23] found that the precipitates on the surface of P. crispus leaves were carbonate-containing hydroxylapatite by scanning electron microscopy (SEM) and energy-dispersive X-ray spectrometry (EDX). Furthermore, the photosynthesis-induced calcium and phosphorus coprecipitation of submerged macrophytes, showed as calcium phosphorus (HCl-P) in total ash phosphorus [10], can effectively reduce the phosphorus content in water [14,21], and there are significant interspecific differences in the HCl-P between Ceratophyllum demersum L. and P. crispus [14].…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown for the freshwater benthic rhizophyte Chara spp. (Murphy et al ., 1983; Kiyosawa, 2001; Siong & Asada, 2006; Kufel et al ., 2013, 2015; Sand‐Jensen et al ., 2018, 2021), and also in CaCO 3 incrustation on the upper leaf surface of the submerged flowering plant Potamogeton crispus (Liu et al ., 2016). The investigation by Sand‐Jensen et al .…”
Section: Calcium Phosphate Incorporation In Extracellular Calcium Car...mentioning
confidence: 99%